Electoral Reform Through the Indonesian Constitutional Court: Constitutionality of Presidential Candidacy Threshold in Indonesia - Djayadi Hanan; Tri Sulistianing Astuti; Luthfi Widagdo Eddyono (Jurnal Konstitusi)
The Indonesian Constitutional Court has emerged as the electoral reform avenue, substantially changing Indonesia’s electoral governance. After 20 years of the presidential threshold norm existing in Indonesia, the Court issued Decision Number 62/PUU-XXII/2024, which abolished the presidential threshold to fulfill the constitutional rights of citizens. This study aims to reveal why the Court shifted its stance and what is its possible implication on reform in the country using the normative juridical method. The study found that the Court decision reflects the Court’s alignment towards representativeness values rather than governability. In addition, politicians lose control over the judicial decision in the presidential threshold. The Court’s decision is possible to shift because the Court was looking at the adverse consequences of the rules, not only to the textual interpretation of the Constitution and its original intent, thus becoming an avenue for electoral reform actors with less political power, such as ordinary citizens, NGOs, and minority political parties outside the parliament as well as those that not involved in parliamentary review during the election law making process.